Type and Severity of Migraine Determines Risk of Atrial Fibrillation in Women - Tae-Min Rhee; Eue-Keun Choi; Eue-Keun Choi; Kyung-Do Han; Hyo-Jeong Ahn; So-Ryoung Lee; Seil Oh; Seil Oh; Gregory Y. H. Lip; Gregory Y. H. Lip; Gregory Y. H. Lip (Frontiers in Cardiovascular Medicine, 2022)
ObjectiveTo evaluate sex differences in the risk of atrial fibrillation (AF) according to the type and severity of migraine.MethodsWe analyzed the nationwide health screening recipients in 2009 without previous AF diagnosis from the Korean National Health Insurance Service data. The diagnosis, type, and severity of migraine were determined using claims data. Newly developed AF was identified during a 10-year follow-up. Sex-difference in the effect of migraine on AF was evaluated.ResultsA total of 4,020,488 subjects were enrolled from January 1, to December 31, 2009 and followed-up through December 31, 2018; 4,986 subjects had migraine with aura (age 50.6 ± 14.0 years, men 29.3%); and 105,029 had migraine without aura (age 51.6 ± 14.3 years, men 30.9%). Risk of AF in a mild degree of migraine was similar to that in the control group, regardless of sex or the presence of aura. Severe migraine without aura modestly but significantly increased the risk of AF in both men and women compared to controls, with increase in AF risk being most prominent in women who had severe migraine with aura [incidence rate (IR) = 3.39, hazard ratio (HR)adjust = 1.48, 95% confidence intervals (CI) = 1.18–1.85]. No significant association according to aura was observed in men with severe migraines (p for interaction 0.011).ConclusionSevere migraine with aura significantly increased the risk of incident AF in women, but not in men. Surveillance for incident AF and prompt lifestyle modification may be beneficial, particularly for young women suffering from severe migraine with aura.